Accessory bones of the feet: Radiological analysis of frequency - Vasiljević Vladica; Marković Ljubo; Vasić-Vilić Jasenka; Mihajlović Đura; Nikolić Bojan; Milošević Saša (Vojnosanitetski Pregled)
Background/Aim. Accessory bones are most commonly found on the feet and they represent an anatomic variant. They occur when there is a failure in the formation of a unique bone from separated centre of ossification. The aim of this study was to establish their frequency and medical significance. Methods. Anteroposterior and lateral foot radiography was performed in 270 patients aged of 20-80 years with a history of trauma (180) and rheumatology disease (90). The presence and distribution of accessory bones was analysed in relation to the total number of patients and their gender. The results are expressed in numeric values and in terms of percentage. Results. Accessory bones were identified in 62 (22.96%) patients: 29 (10.74%) of them were found in female patients and 33 (12.22%) in males. The most common accessory bones were as follows: os tibiale externum 50%, os peroneum 29.03%, ostrigonum 11.29%, os vaselianum 9.68%. Conclusion. Accessory bones found in 23% of patients with trauma and some of rheumatological diseases. Their significance is demonstrated in the differential diagnosis among degenerative diseases, avulsion fractures, muscle and tendon trauma and other types of injuries which can cause painful affection of the foot, as well as in forensic practice.